(untitled) (Journal of the Spanish Institute for Strategic Studies, 2018)
This article proposes a non-conventional approach to the issue of political elites and the internal structures of power in Iran. Based on some influential authors from critical theory, the text explains the ideas behind the Islamic Revolution, the nature of the state and the rationale nurturing the ruling class. After a brief inquire into the current economic context of this oil-rich republic, we will sketch the main features of this Persian-Azeri society which struggles between political agency and an acute alienation from the religious authorities. Finally, we will attempt a «who’s who?» In the geopolitical relations of the IRI with a special focus on how the ongoing conflicts in the Middle East are shaping the elites and perhaps even shifting the global centers of power.